Beyond Technological Fixes: Plastic Pollution Pathways, Recycling Inovtions, and Governance - Fatma Lutfiyatus Sayyida; Raihan Faiq Rahmatullah; Abraham A.Abenego (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
The exponential growth in global plastic production over the past half-century has transformed synthetic polymers from industrial conveniences into one of the most pervasive anthropogenic pollutants on Earth. This study conducts a cross-domain systematic synthesis to evaluate the current state of plastic pollution research and recycling innovations, identifying critical knowledge gaps and strategic pathways for scalable mitigation. Following PRISMA guidelines, we systematically appraised 442 peer-reviewed systematic, scoping, and bibliometric reviews published between 1999 and 2026 across five thematic domains: Amazonian ecosystem contamination, recycling technologies, coastal tourism impacts, pyrolysis-based fuel conversion, and recycled plastics in construction. Results demonstrate widespread microplastic infiltration across remote environments alongside measurable improvements in mechanical and chemical recycling efficiency. However, commercial scalability remains constrained by feedstock heterogeneity, high capital expenditures, fragmented market demand, and a pronounced geographic imbalance in research capacity. The synthesis reveals that technological advancement alone is insufficient to resolve the crisis. Effective mitigation requires integrated governance frameworks, standardized material certifications, extended producer responsibility policies, and equity-centered implementation strategies that prioritize vulnerable communities. By consolidating fragmented evidence into a unified analytical framework, this study provides actionable insights for policymakers, industry stakeholders, and researchers. Aligning future research trajectories with global sustainability commitments is essential to transition from diagnostic awareness to measurable, systemic environmental outcomes.